Usability Evaluation of RAD-Based Production Monitoring Systems in Automotive Manufacturing Using System Usability Scale Method - Tiaraningsih; Nugroho, Agung; Karsito (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
The rapid adoption of digital monitoring tools in the automotive sector often prioritizes technical deployment speed over user-centric design, leading to potential operational inefficiencies. This study evaluates the usability of a production monitoring system developed through Rapid Application Development (RAD) at an automotive manufacturing plant. Utilizing a purposive sampling of 20 active users comprising 15 shop-floor operators and 5 supervisors. This research employs the System Usability Scale (SUS) to quantify user experience post-implementation. Data integrity was rigorously verified through SPSS, yielding a Cronbach’s Alpha of 0.842, which confirms the high reliability of the evaluation instrument. The findings reveal an overall average SUS score of 71.25, categorized as Acceptable with a Good adjective rating and a Grade C classification. Despite this favorable total score, a notable disparity exists between user groups; supervisors rated the system at 74.0, while operators, who manage high-frequency data entry, provided a lower average of 68.5. This result underscores a usability friction inherent in rapidly developed systems that may hinder long-term industrial sustainability. The study concludes that while the RAD-based architecture meets professional functional standards, iterative refinements focusing on reducing interface complexity for operators are essential to minimize human error and optimize production performance.